Regional Level Covid-19 Handling Policy with Autonomy Approach in Garut Regency - Mulyaningsih mulyaningsih (Universitas Pancasakti Tegal, 2021)
There are many government policies in overcoming pandemics, starting with social distancing, working from home for most state civil servants, eliminating worship activities, staying at home movements, and reducing economic activity outside the home. However, the spread of the virus continues to increase, and the policy continues with the Enactment of Restrictions on Community Activities (PPKM). Implementing the Garut district government's approach seeks to lower the level of PPKM by implementing rules that can prevent and break the chain of transmission of the COVID-19 outbreak. The concept of Regional Autonomy can answer the current problems of local government bureaucracy if its implementation is adjusted to economic, social, political, and cultural conditions. This research uses a type of qualitative research with an exploratory approach. The results showed that local-level government through regional autonomy has a significant role, especially in handling covid-19. The implementation of policies at the central level must be executed quickly and appropriately by local governments. Autonomy exerts a substantial influence on the change of governance at the regional level.